Seasonal increase of nest height of the Silver-throated Tit (Aegithalos glaucogularis): can it reduce predation risk? - Haohui Guan; Ye Wen; Pengcheng Wang; Lei Lv; Jiliang Xu; Jianqiang Li (Avian Research, 2018)
Abstract Background Nest predation is usually the main cause of bird nest failure. ‘Predation avoidance hypothesis’ of nest-site selection predicts that birds should prefer nest-sites with higher nesting success. We investigated the relationship between nest height and nest fate in Silver-throated Tits (Aegithalos glaucogularis) and asked whether the seasonal change of nest height was adaptive by simultaneously analyzing the seasonal variation of predation rates of the nests. Methods We monitored nests of the Silver-throated Tit across seven breeding seasons in the Dongzhai National Nature Reserve in Henan Province of China. We compared the difference of nesting success among nests of different heights and analyzed the effect of nesting date on nest height and nest predation rates. Results The overall nesting success rate was 24.1% (n = 623). Among the failed nests (n = 472), 59.75% were predated by birds and mammals, followed by snakes (9.11%). The average height of successful nests was significantly lower than that of predated nests. As the season progresses, the height of the nests increased significantly, companied by the decrease in nesting success. Daily survival rate of the nests also decreased with the progression of the season, regardless of breeding stages. Conclusions Our findings suggest that nest height is an important factor influencing the nesting success of Silver-throated Tits. However, the seasonal increase of nest height appears inconsistent to the ‘predation avoidance hypothesis’, because it is associated with higher predation rates. The reason for this maladaptive behavior remains to be explored in future studies.